Identification of collision risk factors perceived by ship operators in a vessel encounter situation. (15th March 2020) - Kim, Do-Hoon
Abstract: This study aims to elucidate the possible risk factors considering the point of view of a ship operator by identifying the maximum collision risk-bearing angle (MCRBA) and the distance at which the collision risk begins to increase significantly (DCRBIS), which are key factors affecting navigation safety in real maritime environments. Using two ships at sea in various vessel encounter situations (relative bearing angles of 000°, 045°, 090°, and 135°), the perceived ship collision risk (PSCR) was estimated by the ship operators. Then, the mean values of all the measured parameters were used to identify the bearing angle corresponding to the highest PSCR. The MCRBA was compared to the maximum frequency collision bearing angle (MFCBA) derived by investigating 200 reported ship collision cases in Korean waters. The highest experimental PSCR values were observed at a relative bearing angle of 135°, which corresponded to the results of collision case analyses stating that the MFCBA was equal to 112.5°–135°. Notably, the PSCR magnitude increased most significantly at a distance of 1.25–1 NM in experiments involving various vessel encounter situations. Collision risk factors such as the MCRBA and DCRBIS can thus be used in the development of collision prevention protocols for ship operators. Highlights: Effect of human factors on ship collision probability is investigated. Maximum collision risk-bearing angle & distance is identified. Four different ship encounter situations are examined experimentally. Highest ship collision risk is perceived at a relative bearing angle of 135°.